2007
DOI: 10.1083/jcb.200706015
|View full text |Cite
|
Sign up to set email alerts
|

Bub1 mediates cell death in response to chromosome missegregation and acts to suppress spontaneous tumorigenesis

Abstract: The physiological role of the mitotic checkpoint protein Bub1 is unknown. To study this role, we generated a series of mutant mice with a gradient of reduced Bub1 expression using wild-type, hypomorphic, and knockout alleles. Bub1 hypomorphic mice are viable, fertile, and overtly normal despite weakened mitotic checkpoint activity and high percentages of aneuploid cells. Bub1 haploinsufficient mice, which have a milder reduction in Bub1 protein than Bub1 hypomorphic mice, also exhibit reduced checkpoint activi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

12
281
0
2

Year Published

2009
2009
2019
2019

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 205 publications
(300 citation statements)
references
References 56 publications
(98 reference statements)
12
281
0
2
Order By: Relevance
“…Coincident with downregulation of PLK1, several members involved in the mitotic checkpoint function remained also down-regulated in treated cells. Partial loss of checkpoint control by such genes has often been associated to abnormal mitosis (Jeganathan et al 2007). Among the down-regulated mitotic checkpoint gene members detected in this work, it is noteworthy the down-regulation of HEC1 gene.…”
Section: Discussionmentioning
confidence: 99%
“…Coincident with downregulation of PLK1, several members involved in the mitotic checkpoint function remained also down-regulated in treated cells. Partial loss of checkpoint control by such genes has often been associated to abnormal mitosis (Jeganathan et al 2007). Among the down-regulated mitotic checkpoint gene members detected in this work, it is noteworthy the down-regulation of HEC1 gene.…”
Section: Discussionmentioning
confidence: 99%
“…We first examined MEFs with graded reduction in Bub1 expression (14). Western blot analysis demonstrated that levels of Ser18-phosphorylated p53 and p21 were indeed elevated in Bub1 H/H and Bub1 H/− MEFs, but not in wildtype or Bub1 +/H or Bub1 +/− cells (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Cdc20 AAA mice were described previously (19) and were crossed with p53 knockout mice (a generous gift from L. Donehower at Baylor College of Medicine, Houston) to produce double-mutant mice. Bub1-deficient mice were generated previously (14). Atm-deficient mice were originally generated by Barlow et al (30) and were obtained from C. Zhu at MD Anderson Cancer Center, Houston.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…[23][24][25][26][27][28] However, mice heterozygous for Mad1 and Mad2 or mice with the hypomorphic alleles of BubR1 (BubR1 H ), Bub3 (Bub3 H ), and Bub1 (Bub1 H ) develop either late onset of spontaneous tumors or early aging-associated phenotypes, whereas heterozygous mice for Bub1, Bub3, and BubR1 show no obvious phenotypes. 23,27,[29][30][31] Importantly, mice overexpressing Mad2 also show accelerated tumorigenesis with chromosomal instability. 11,12 These results suggest that a threshold level of the mitotic checkpoint-related proteins is necessary for preventing cells from chromosome missegregation, tumor development, and aging-associated phenotypes.…”
Section: Discussionmentioning
confidence: 99%